ANALYZING THE ROLE OF EMPLOYEE ENGAGEMENT ON SERVICE QUALITY IN COMMERCIAL BANKS (International Journal of Food and Nutritional Sciences, 2023)
This descriptive research paper explores the role of employee engagement in influencing service quality within commercial banks. Employee engagement, which refers to the emotional commitment and involvement of employees in their work